Update on radioligand therapy with 177Lu-PSMA for metastatic castration-resistant prostate cancer: clinical aspects and survival effects. Issue 4 (August 2022) - Fuoco, Valentina; Argiroffi, Giovanni; Mazzaglia, Stefania; Lorenzoni, Alice; Guadalupi, Valentina; Franza, Andrea; Scalorbi, Federica; Aliberti, Gianluca; Chiesa, Carlo; Procopio, Giuseppe; Seregni, Ettore; Maccauro, Marco
Objective: To give an updated overview on clinical aspects and survival effects of lutetium-177–prostate-specific membrane antigen (PSMA) ( 177 Lu-PSMA) radioligand therapy (RLT), a novel treatment option for patients with metastatic castration-resistant prostate cancer (mCRPC). Methods: PubMed/MEDLINE database was searched for relevant articles published up to March 2021. The search was restricted to English-language articles. Results: Current evidence from the literature consistently demonstrated the efficacy, safety, and survival benefit of 177 Lu-PSMA RLT in mCRPC. However, current data rely predominantly on retrospective analyses, showing heterogeneity of patient population and treatment protocols. More recently, results from the first randomized phase II study (TheraP) demonstrated that 177 Lu-PMSA therapy significantly improved prostate-specific antigen response rate (66% vs 37%) and had fewer grade 3/4 adverse events when compared to cabazitaxel in patients with docetaxel-pretreated, progressive mCRPC. This review is intended to provide an updated overview of treatment protocols and responses, toxicity profile, and survival effects of 177 Lu-PSMA RLT. Conclusions: 177 Lu-PSMA RLT has emerged as a promising targeted treatment in mCRPC. It is currently applied in compassionate use programs and following exhaustion of approved therapies. Crucial for establishing this treatment in routine clinical management will be the results of the phase III VISION trial, which may confirm the encouraging patient outcomes reported to date.